Level of knowledge, competence and interest of agronomists in digitalisation of agriculture in Croatia - Sanja Jelić Milković; Ružica Lončarić; Dominik Tačković; Iva Nikolin; Zdenko Lončarić (Journal of Central European Agriculture)
The aim of this paper was to investigate the current level of knowledge, competence and interest of agronomists in participating in the digitalisation of agriculture in Croatia, as well as the role of some stakeholders in training the farmers since it can be assumed that agronomists will play a significant, perhaps even decisive role in the process of digitalisation of agriculture in Croatia. Primary data were collected through a survey using an online questionnaire (n = 80) as a research tool. The target group of respondents were agronomists, regardless of their age and occupation. According to the research findings, 20.0% of respondents have some difficulties in using digital technologies, while 12.5% of respondents do not use digital technologies at all. On the 5-point agreement scale (1 to 5), respondents rated the importance of agronomists in the digitalisation of agriculture at 4.54, their personal interest in participating in digitalisation at 4.38, and their current competence for digitalisation at 3.09. The main conclusions are that the majority of respondents believe that: 1. Agronomists are important and well-trained to participate in the digitalisation process of Croatian agriculture.; 2. Faculties, extension services, the Chamber of Croatian Agronomists, distributors and producers of software and digital equipment should play a key role in providing additional training in digital skills.; 3. Knowledge of digital technologies is equally important for medium and large farms as well as for state units.